Social determinants of self-rated health and cardiovascular disease among the Sami and other Arctic indigenous peoples. The SLiCA study and the SAMINOR study - Eliassen, Bent-Martin (University of Tromsø, 2013)
Paper 3 of this thesis is not available in Munin: 3. Eliassen BM, Graff-Iversen S, Melhus M, Hansen KL, Løchen ML and Broderstad AR.: 'Ethnic difference in the prevalence of angina pectoris in Sami and non-Sami populations: The SAMINOR study' (manuscript) The post-World War II years in the Arctic were characterised by an intensification of sociocultural change. Previous studies among indigenous peoples show that colonialism, rapid modernisation and subsequent marginalisation and sociocultural change are accompanied by overall ill health and a negative cardiovascular risk profile and disease burden. Paper I showed that aggregate acculturation was a strong risk factor for poorer SRH among the Greenlandic Inuit and female Iñupiat of Alaska.Paper II (n=4027) showed that marginalised Sami living in Norwegian dominated areas were more than twice as likely (OR 2.10) as non-marginalised Sami from Sami majority areas to report lifetime CVD. Moderate to no intermediate effects were seen after including established CVD risk factors, which suggest little difference in lifestyle related factors. Chronic stress exposure following marginalisation may however be a plausible explanation for some of the observed excess of CVD. Paper III (n=15,206) showed an excess of angina pectoris symptoms (APS), self-reported angina, and a combination of these in Sami women and men relative to non-Sami women and men. Total cholesterol, metabolic syndrome, smoking, family history of cardiovascular disease, and moderate alcohol consumption explained little or none of the ethnic variation in APS. The excess burden of APS was in Sami women principally due to known cases of angina pectoris. In men however the discrepancy in prevalent angina symptoms may be due to an excess burden of undiagnosed disease among the Sami. These results may indicate under-utilisation of health care services among Sami men which suggest that social determinants play a role in the distribution of APS in this population. The results in Paper II also suggest that ...